Enzymatic Processes Triggered by PEF for Astaxanthin Extraction From Xanthophyllomyces dendrorhous - Aguilar-Machado, Diederich; Delso, Carlota; Martinez, Juan Manuel; Morales-Oyervides, Lourdes; Montañez, Julio; Raso, Javier (Frontiers in Bioengineering and Biotechnology, 2020)
The aim of this study was to evaluate the potential of pulsed electric fields (PEF) to improve the extraction of astaxanthin from fresh biomass of a wild-type (CECT 11028) and mutant (ATCC 74219) Xanthophyllomyces dendrorhous strain using ethanol as solvent. Inactivation and propidium uptake studies revealed that inactivation is a good index for estimated the proportion of irreversible permeabilized cells when inactivation is higher than 70% in the two strains. Ethanol was ineffective for extracting carotenoids from the PEF-treated cells (20kV/cm, 135 µs) of the two strains. However, after aqueous incubation of PEF-treated X. dendrorhous ATCC 74219 cells for 12 hours, up to 2.4 mg/g d.w. of carotenoids were extracted in ethanol. From the recovered carotenoids, 84 % corresponded to trans-astaxanthin. The occurrence of esterase activity in the supernatant and the relationship between the percentage of esterase activity quantified and the amount of carotenoids extracted indicate that the extraction of astaxanthin was mediated by enzymatic esterase activity triggered by PEF during incubation. On the other hand, the formation of a large lipid globule into the cytoplasm of PEF-treated X. dendrorhous CECT 11028 cells during aqueous incubation prevented carotenoid extraction. The process developed in this investigation represents a more sustainable and greener method that those previously used for extracting astaxanthin from yeast.